Understanding Chile's Social Unrest in an International Perspective - Hadzi-Vaskov, Metodij (IMF Working Papers; Working Paper, 2021)
We aim to provide a broad descriptive overview of Chile's social issues, in comparison to other countries and over time, in order to place the recent social unrest in historical and international perspectives which can help prepare the ground for future policy priorities. We follow an eclectic approach, classifying a broad set of indicators along six dimensions-inequality across: i) income; ii) perception; iii) access; iv) opportunity; v) redistribution; and vi) location. The analysis puts forward a set of descriptive findings. First, income inequality declined substantially but remains high, also compared to countries with similar level and path of development. Second, Chile seems to be one of the few countries in Latin America with declining inequality where perceived inequality actually increased. Third, notwithstanding an increase in social spending, access to essential services appears limited, particularly for middle and lower income classes, amid fast growth of out-of-pocket health expenses, relatively faster growth of cost of living for the relatively poorer, and remaining weaknesses in the pension and education systems. Fourth, inequality of opportunity is high, with limited competition. Fifth, fiscal redistribution has improved markedly, but remains low by international standards. Finally, inter-regional inequality has declined substantially over the last two decades, reaching levels similar to the OECD median.